The use of Red Onion (Allium Cepa L.) Skin Extract as an Antioxidant and Anti-Inflammatory in Rats: A Literature Review Study - Gede Agus Ari Tirtayasa; Maria Malida Vernandes Sasadara; Putu Era Sandhi Kusuma Yuda; Erna Cahyaningsih; Ni Luh Kade Arman Anita Dewi (CV Edujavare Publishing, 2026)
Red onion peel (Allium cepa L.) is an agricultural by-product that contains high levels of bioactive compounds, particularly flavonoids and quercetin, which are known to possess antioxidant and anti-inflammatory properties. This systematic literature review aims to analyze the scientific evidence regarding the effects of red onion peel extract on antioxidant and anti-inflammatory activities in mouse models. Data were collected from international databases and selected based on relevance to in vivo and in vitro studies published between 2020 and 2025. The findings indicate that red onion peel extract significantly enhances antioxidant defense mechanisms by increasing the activity of superoxide dismutase (SOD), catalase, and total antioxidant capacity (ORAC), while reducing oxidative stress markers such as nitric oxide (NO) and inducible nitric oxide synthase (iNOS). In addition, the extract exhibits strong anti-inflammatory effects through the suppression of pro-inflammatory cytokines, including IL-1α, IL-1β, IL-6, and TNF-α, as well as inhibition of key signaling pathways such as JAK-STAT, NF-κB, and NLRP3/caspase-1. The effectiveness of the extract is influenced by dosage, duration of administration, and extraction method, with higher doses and longer exposure generally producing stronger biological effects. Overall, red onion peel extract shows promising potential as a natural source of antioxidant and anti-inflammatory agents for nutraceutical and therapeutic applications.